Simulação de sistemas de simples estágios de refrigeração por compressão de vapor - ZIGMANTAS, Paulo Vitor de Matos (Universidade Federal do Pará, 2012)
Nowadays, the thermal performance of refrigeration systems of vapor compression is a very important toll to aid on the development of News Products or Upgrading them. A steady state simulation model is presented to estimate the refrigeration systems performance.The studied system considers a air conditioning equipment Model PA HILTON, that includes a semi-hermetic alternative compressor, a compact tube and fins evaporator and condenser and finally a thermostatic expansion valve. The condenser mathematical model takes account of three different regions of heat transfer : cooling, condensing and sub-cooling.The evaporator mathematical modeling considers the evaporating and superheated regions. Depending of the region studied, in the model simulated includes appropriate correlations of heat transfer and pressure droops. The heat transfer and pressure drop inside the lines between the components are not considered. The solution of non linear equation systems is obtained trough a interactive method using the Engineering Equation Solver Software. The comparations between experimental and simulated values shows a very good agreement.